The reality of using Future Portal Platform in the educational process from the viewpoint of the teachers of Sabya Education Department - Al-Muharraq, Shamea Hassan; Al-Zahrani, Hassan Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the pros and cons of using Future Portal Platform in the educational process from the viewpoint of the teachers of Sabya Education Department, and its role in solving the educational problems suffered by Sabya Education Department, in addition to revealing the impact of some demographic variables for the teachers of Sabya Education Department based on the reality of their using Future Portal Platform. In order to achieve the study objectives, the descriptive approach has been used. The study population consisted of all the teachers of intermediate and secondary schools of educational offices affiliated to Sabya Education Department who use Future Portal Platform totaling (1151) teachers. The study’s main sample consisted of (206) teachers who have been chosen by the simple random method, while the questionnaire has been used as a tool to collect data, and after conducting statistical analyzes, results showed: That the study sample estimates for the pros of using Future Portal Platform in the educational process came at a high degree, while their estimates of the obstacles of its use were very high, and that (62.1%) of the study sample believe that Future Portal will contribute to solving the educational problems suffered by Sabya Education Department. The results also revealed that there are statistically significant differences between the means of the teachers estimates for the two dimensions (administrative obstacles, obstacles related to the skills needed to use Future Portal) affiliated to the variable of the years number of using the technology for educational purposes, and there are statistically significant differences between the means of the teachers estimates for the pros of using Future Portal Platform in the process attributed to the two variables (the stage in which the school choose to use Future Portal Platform, the receipt of formal training to use Future Portal), and in light of these results, the researchers made a number of recommendations, including: To hold seminars and workshops for teachers of different schools to provide them with modern trends in teaching and training them on how to employ electronic learning platforms in the educational process and explain their pros.